PRAGMALINGUISTIC FEATURES OF SPEECH ACTS IN CONTEXT (Ustozlar uchun, 2025)
This study investigates the pragmalinguistic features of speech acts as they function within various contextual settings. Using corpus analysis combined with pragmatic theory, the research scrutinizes how context influences the interpretation and realization of speech acts. Data drawn from everyday conversational exchanges and formal interactions reveal patterns and strategies speakers utilize to convey intentions effectively. The findings contribute to better understanding the interplay between linguistic form, pragmatic function, and situational context, enhancing applied linguistics, intercultural communication, and language teaching.